Role of Ultrasound in Early Detection of Molar Pregnancy - Ahmad, Adnan; Mehreen Samad; Ahmad, Sadia; Tamkeen, Naila; Wahid, Ghazala; Ahmad, Naveed (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES The objective of this study was to investigate the role of ultrasound in the detection of early pregnancies presenting with placental molar changes. METHODOLOGY This retrospective study was carried out at Radiology department of Hayatabad Medical Complex, Peshawar, between Aug 2020 and July 2021. All cases suspected of molar changes were evaluated from 10-14 weeks of gestation. The patient were referred to our department because of fetal abnormality, maternal disease or age and family or previous pregnancy history or were identified from an ongoing ultrasound screening study for aneuploidy by measurement of fetal nuchal translucency thickness. Transabdominal or transvaginal sonography was used to examine the fetus and placenta. RESULTS Total 85 patients of molar pregnancies were enrolled in the study. Age ranged between 20-45 years with a mean age of 32.5 years. There were 60(70.6%) complete moles (CM) and 25(27.4%) partial moles (PM) were suspected on ultrasound. In case of complete mole coexisting with a normal singleton or twin pregnancy, the molar placenta was clearly separated from the normal placenta, whereas with partial moles the molar structures were dispersed inside the placental mass. CONCLUSION Ultrasound detection of molar pregnancy remains a diagnostic challenge. Data suggest that there has been an increase in both the predictive value and the sensitivity of ultrasound over time; however, the diagnostic criteria remain ill defined. Prior to managing a miscarriage, being aware of the possibility of molar pregnancy will guide treatment and allow for adequate follow-up.